Answer:
7^11
Explanation:
There is a rule for simplifying exponents: n^a + n^b = n^a+b.
The rule applies here too. 7 is the n and the exponents on top are a and b. Following the rule:
![{7}^(8) * {7}^(3) = {7}^(8 + 3) = {7}^(11)](https://img.qammunity.org/2022/formulas/mathematics/high-school/s2namx59joxcaf00wjxjyqkufn6krgsmyc.png)
Then you continue this formula:
11+4-9+5 = 11
Since the end result is 11 the answer is
![{7}^(11)](https://img.qammunity.org/2022/formulas/mathematics/high-school/rpnhp9pleki2bj4a85ua3uhqcjfjg2lyub.png)